A broad, exposome-type evaluation of xenobiotic phase II biotransformation in human biofluids by LC-MS/MS. Issue 1 (12th October 2022) - Fareed, Yasmin; Braun, Dominik; Flasch, Mira; Globisch, Daniel; Warth, Benedikt
Abstract: Xenobiotics are chemicals foreign to a specific organism that humans are exposed to on a daily basis through their food, drugs, and the environment. These molecules are frequently metabolized to increase polarity and subsequent excretion. During sample preparation, deconjugation of phase II metabolites is a critical step to capture the total exposure to chemicals in liquid chromatography mass spectrometry (LC-MS) assays. Knowledge on deconjugation efficiencies of different enzymes and the extent of conjugation in human biofluids has primarily been investigated for single compounds or individual chemical classes. In this study, the performance of three β-glucuronidase and arylsulfatase mixtures from Helix pomatia, from recombinant sources (BGS™), and from Escherichia coli combined with recombinant arylsulfatase (ASPC™) was compared and the efficiency of phase II deconjugation was monitored in breast milk, urine, and plasma. An innovative LC-MS/MS biomonitoring method encompassing more than 80 highly diverse xenobiotics (e.g., plasticizers, industrial chemicals, mycotoxins, phytoestrogens, and pesticides) was utilized for the comprehensive investigation of phase II conjugation in breast milk and urine samples obtained from breastfeeding women. Overall, it was confirmed that H. pomatia is the most efficient enzyme in hydrolyzing different classes of xenobiotics for future exposome-scale biomonitoring studies. The recombinant BGS™ formulation, however, provided better results for breast milk samples, primarily due to lower background contamination, a major issue when employing the typically applied crude H. pomatia extracts. A deeper understanding of the global xenobiotic conjugation patterns will be essential for capturing environmental and food-related exposures within the exposome framework more comprehensively.